Chapter 8 Peter Rehberg, Christian Fennesz and the Label Mego Between Glitch and Bécs - Mazierska, Ewa (Taylor & Francis, 2018)
A large proportion of artists considered in this study at some stage of their career veered towards 'serious' or experimental music. This also refers to Peter Rehberg and Christian Fennesz. However, they differ from those considered previously, because unlike them, they did not cross the boundary between the popular and academic now and then but made it their personal signature. Their music also challenges our concept of electronic music, as well as studio and stage and even music and non-music. To contextualise their work, it is worth locating it first against the concept of 'noise music' or rather 'noise as music'.